COVID-19: An Unexpected and Unusual Driver to Online Education - Amemado, Dodzi (International Higher Education, 2020)
COVID-19 is creating havoc and contributing to a social panic that has led to a temporary closure of most campuses across the globe. It has become impossible to meet face-to-face for on-campus course delivery and in-person interactions, using the university’s physical setting for intellectual and academic pursuits. This article discusses the implications of the shift to online education for higher education.